Efeito da hemólise sobre o perfil bioquímico sérico canino, bovino e equino - Almeida, B. F. M. [UNESP]; Zucatto, A. S. [UNESP]; Vieira, R. F. C.; Soeiro, C. S. [UNESP]; Viol, M. A. [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Ciarlini, Paulo Cesar [UNESP] (Univ Federal Rural Pernambuco, 2011)
Hemolysis is the main cause of biochemical analysis rejection's in veterinary laboratories, however the relative error caused by hemoglobin on serum biochemical profile has not been properly established on several species. In order to establish criteria for aproval and rejection of hemolyzed samples for serum biochemical tests, the hypothesis that hemolysis causes biochemical changes in canine, cattle and horses and that laboratorial error depends on species and hemolysis degree was tested. Thus, non-hemolyzed serum was contaminated with crescent hemoglobin levels and using commercial routine reagents, the serum concentrations of uric acid, albumin, cholesterol, triglycerides and urea, besides the activity of ALT, AST, CK and GUT were quantified in triplicate samples. The relative error was calculated by the comparison between hemolyzed and non-hemolyzed samples. Hemolys is did not cause significant error on the albumin determination in all three species, AST in canine and cattle, ALT in horses, UK and cholesterol in canine. There was a linear increase on uric acid levels in horses and cattle, triglycerides in all three species. A linear increase in serum urea in all species serum, UK and cholesterol in cattle and cholesterol in horses was observed. Serum AST activity on equine serum and ALT in cattle decreased linearly due to hemolysis. It was concluded that hemolysis promotes changes in canine, equine and bovine serum chemistry profile, however the laboratorial error not necessarily compromises the diagnosis in all cases, because the changes depends on species and degree of in vitro hemolysis.
Effect of hemolysis on canine, bovine and earn e serum chemistry
Keywords: hemoglobin; blood profile; laboratory error; quality control